ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PENYERAPAN TENAGA KERJA PADA INDUSTRI KECIL TAPE DI KABUPATEN BONDOWOSO - ., Mashuda; Arief, Sjamsul (Fakultas Ekonomi Universitas 17 Agustus 1945 Surabaya, Indonesia, 2016)
This study aimed to analyze and examine the influence of the amount of production and the number of business units on employment in small industries in the District Bondowoso good tape together - together or partially. Types and sources of data using a quantitative approach with secondary data from relevant agencies such as the Central Bureau of Statistics East Java Province and the Central Bureau of Statistics regency. The research variables consisted of a dependent variable absorption of labor (Y). Independent variables are the amount of production (X1), and a number of business units (X2). Data analysis tools using multiple linear regression method, t-test, f and the coefficient of determination. Based on the results of multiple linear regression analysis obtained the following results: Y = 44.495 + 4,895E - 7X1 + 2,478X2 + e. Retrieved also tcount total production amounted to 3.629 and the number of business units amounted t 5,416 with ttabel 2.3646. While simultaneously testing the obtained value of Fcount 69.609 > 4.74. Thus H0 is rejected and Ha accepted. The results showed that both independent variables can contribute to employment in District Bondowoso so the government should pay more attention to the sustainability of small industrial tape in the regency.Keywords: Absorption of Labor, Total Production, Total Business Unit.